2022
DOI: 10.1002/cmdc.202100780
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Fluorescent Heptamethine Cyanine Dyes for COX‐2 Targeted Photodynamic Cancer Therapy

Abstract: We designed and synthesized two heptamethine cyanine-based theranostic probes that aimed to target COX-2 in cancer cells. One is I-IR799-CXB, in which I-IR799 is conjugated to the COX-2-specific inhibitor, celecoxib, and another is I-IR799-IMC, where the non-selective COX inhibitor, indomethacin, was used. I-IR799 is a heptamethine cyanine derivative that can be activated by near-infrared light for photodynamic therapy (PDT) purposes. I-IR799-CXB and I-IR799-IMC were tested for their cancer-targeting capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that COX‐2 inhibitors have cancer targetability and direct anti‐inflammatory effects to enhance the antitumor capacity of PDT. [ 20 ] However, few studies focused on the synergistic effect of PDT and COX‐2 inhibitors on immune activation. Given the capacity for ICD induction and PGE 2 and IDO1 downregulation, we further determined T cell infiltration and activation after DHU‐CBA2 treatment with PDT.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that COX‐2 inhibitors have cancer targetability and direct anti‐inflammatory effects to enhance the antitumor capacity of PDT. [ 20 ] However, few studies focused on the synergistic effect of PDT and COX‐2 inhibitors on immune activation. Given the capacity for ICD induction and PGE 2 and IDO1 downregulation, we further determined T cell infiltration and activation after DHU‐CBA2 treatment with PDT.…”
Section: Resultsmentioning
confidence: 99%
“…With the rapid development of PSs in recent years, PDT has been proven to be effective in the anti‐cancer treatment of head and neck cancer, skin cancer and early obstructive lung cancer [7] . As far as we know, some traditional fluorophores like tetrapyrrole cores, BODIPY dyes, [8] and cyanine derivatives [9] have been widely used to construct PSs for the ablation of cancer cells, and even a couple of tetrapyrrole‐based compounds have been approved as drugs for clinical PDT by several governments [10] . However, most of these PSs are hydrophobic and planar, which easily aggregate in the aqueous environment, leading to not only the notorious aggregation‐caused fluorescence quenching (ACQ) effect but also the decreasing photosensitizing efficiency [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Cyanine dyes have electronic states that absorb and emit in the visible and in the infrared parts of the spectrum, they are commercially available and affordable, they are positively charged (which allows them to be used in aqueous media), their toxicities (or those of nanoparticles formed from them) are low enough to be biocompatible, they are functionalizable and most of them are chemically stable [17,37] . Determining the relationship between the structure of a dye and its TPA properties opens the path for cyanines to be used in frontier applications such as photopharmacology, photodynamic therapy, photothermal therapy and high‐resolution 3D imaging [27,38–42] . Certain variables, such as the length of the conjugated chain, have been explored to increase their TPA cross‐sections, but the role of the substitution of the carbons of the chains of equal length has not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Cyanines are widely used in research and development because of their remarkable optical properties, namely their tunable absorption and emission of light. [17][18][19][20] Applications of these synthetic materials include their pioneering use as photosensitizers in photography, [21] and have seen renewed interest in recent years, [22][23][24][25] for example in their use as tissuespecific labeling, [26] as fluorescent probes, [27,28] as standards for IR quantum yield measurements, [29] as donor-acceptor pairs in microscopic distance measurements, [30] as photosensitizers in prodrugs for chemo-phototherapy, [31] as photo-caging groups activated by near-IR light, [32] as saturable absorbers, [33] in telecommunications [34] and in photoremovable protecting groups (PPG) [35] and also their surprising use in the preparation of Bose-Einstein condensates at room temperature. [36] Cyanine dyes have electronic states that absorb and emit in the visible and in the infrared parts of the spectrum, they are commercially available and affordable, they are positively charged (which allows them to be used in aqueous media), their toxicities (or those of nanoparticles formed from them) are low enough to be biocompatible, they are functionalizable and most of them are chemically stable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation